‘Non-Standard’ Political Parties and the Capacity to Govern in Turbulent Times: Slovakia 2020–2022 - Ivan Maly; Juraj Nemec (Transylvanian Review of Administrative Sciences, 2023)
This article evaluates whether the failures of the two coalition governments that presided over Slovakia between March 2020 and September 2022 should be connected primarily to the two crises of the investigated period (COVID-19 and the war in Ukraine), or whether other critical factors were involved. Our findings highlight the limited performance of public administration in Slovakia and the very limited capacity of both governments to govern during the selected period. We confirmed that the coalition governments were created from ‘non-standard’ political parties, and the leadership was problematic. We do not insist that these factors are interrelated, but the possibility should be the focus of further research.